Is Alumni Salary an Appropriate Metric for University Marketers? - Masciantonio, Tanya A; Berger, Paul D (Journal of Social Economics Research, 2018)
This paper considers ethnicity variables and financial variables to study what impact they have on alumni salaries six and ten years after graduation, for colleges and universities in the United States. We find that certain ethnic groups earn less salary both six years out and ten years out, while other ethnic groups earn more salary both six and ten years out. The same is true for selected financial variables, such as median household income. We perform our study primarily using stepwise-regression analyses. Since many colleges and universities use future salary of alumni as a marketing tool, this study cautions that there is a danger to the diversity of a college campus, and a corresponding harm to students on such a campus, if the college or university places too much emphasis on future alumni salary and makes admissions decisions in a way that emphasizes that criterion.